The Role of the Manufacturing Industry in the Economy: Basic Sectors and Input-Output Analysis - Anggara Pratama Putra; Rumayya; Isdiana Fitriyani (Jurnal Ilmu Ekonomi Terapan, 2026)
Objective: This study aims to evaluate the role of the manufacturing sector in the economy of East Java by applying a base sector approach and input–output analysis. The main objective is to assess the extent to which the manufacturing sector acts as a key driver of regional economic growth and generates intersectoral linkages and multiplier effects on output, income, and employment. Design/Methods/Approach: The study adopts a quantitative approach by combining location quotient (LQ) analysis and input–output analysis. The LQ method is used to identify whether manufacturing functions as a base sector in East Java’s economy, while input–output analysis examines the sector’s forward and backward linkages with other sectors. The analytical results are further interpreted in relation to Industry 4.0 and sustainability policy frameworks in East Java. Findings: The findings indicate that the manufacturing sector has an LQ value of 1.40 (>1), confirming its role as a base sector with a substantial contribution to East Java’s gross regional domestic product (GRDP). Input–output analysis reveals strong forward and backward linkages between manufacturing and other sectors. An increase in manufacturing output is shown to stimulate the growth of related sectors and generate significant multiplier effects in terms of output expansion, income generation, and employment creation. Originality/Value: This study contributes to the economic literature by integrating base-sector analysis with input–output analysis while explicitly linking multiplier effects to Industry 4.0 and sustainability policies. This combined approach offers new insights into sectoral interdependencies and illustrates how technological transformation and sustainability initiatives can enhance the competitiveness of the manufacturing sector at the regional level. Practical/Policy implication: The results highlight the importance of policies that prioritize infrastructure development, improved logistics connectivity, and human capital development through vocational education and training aligned with Industry 4.0 technologies. In addition, incentives for green industries, export promotion, and strengthened international cooperation are essential to expand markets and enhance competitiveness. These policy recommendations can be applied to reinforce the manufacturing sector as a strategic pillar for sustainable economic growth in East Java.